Mechanisms and applications of wind turbine blade waste in cementitious composites: A review - Tao Liu; Charilaos Paraskevoulakos; Umair Abid Mughal; Ashal Tyurkay; Nataliya Lushnikova; Helong Song; Ceren Duyal; Shashank Tumkur Karnick; Florent Gauvin; Ana Teresa Lima (Materials & Design, 2025)
The cement and concrete industry play vital roles in global and local economies, and urgent measures are required to minimize carbon emissions. Utilizing end-of-life (EoL) wind turbine blades (WTB) in cementitious matrices —whether as fiber reinforcement, aggregate replacement, or binder material—represents an innovative solution to mitigate environmental impacts. This offers potential due to their rich calcium, silicon, and aluminum content in glass fiber-reinforced polymer (GFRP). The current review paper highlights the fundamental properties of WTBW (waste from wind turbine blades). Waste-cement reaction mechanisms and physical/mechanical properties of WTBW-incorporated cementitious materials are identified and discussed. Environmental implications and future research directions are also discussed. Findings suggest that fibers with epoxy resin from WTBW can increase water absorption by changing pore structure, hindering cement hydration and long-term strength. Epoxy resin may lower pH through hydroxyl ion consumption, delaying hydration, extending setting time, and reducing early strength. Meanwhile, the incorporation of WTBW in cementitious materials includes two main concepts- reinforcement (as fibers) or replacement (as powder, sand, or coarse aggregates). Low WTBW replacement levels (≤10 %) yield optimized mechanical performance, with decreasing performance at higher dosages. This work emphasizes the promise of WTBW in sustainable construction materials.